INSTITUTIONAL MECHANISMS AND THEIR LIMITS: EVALUATING INDIA-CHINA BORDER CONFIDENCE-BUILDING MEASURES (2000–2020) - Ganiger, Santosh Mallappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The India-China border dispute, a persistent geopolitical challenge, has seen numerous institutional mechanisms established between 2000 and 2020 to mitigate tensions through Confidence-Building Measures (CBMs). This study evaluates the efficacy and limitations of these CBMs, analysing their role in fostering stability amidst enduring territorial disagreements. Through qualitative examination of bilateral agreements, diplomatic engagements, and conflict incidents, the paper assesses key frameworks such as the 1996 Agreement on Confidence-Building Measures, the 2005 Protocol on Modalities, and the 2013 Border Defence Cooperation Agreement. Findings reveal that CBMs facilitated crucial communication channels—including hotlines, joint military exercises, and high-level dialogues—which temporarily eased friction and managed crises like the 2013 Depsang standoff. However, recurrent clashes, notably the 2017 Doklam crisis and the lethal 2020 Galwan Valley conflict, underscore institutional shortcomings. Limitations stem from unresolved territorial claims, ambiguous perceptions of the Line of Actual Control (LAC), and inadequate enforcement mechanisms. Bureaucratic inertia, slow adaptation to on-ground realities, and a deficit of mutual political trust further weaken CBM implementation. The study concludes that while CBMs are vital for crisis management, their utility remains constrained without addressing core disputes. Sustainable peace necessitates integrating CBMs with robust diplomatic efforts to resolve territorial ambiguities and foster deeper strategic trust. The paper advocates for agile, transparent institutions complemented by political dialogue, highlighting the interplay between procedural mechanisms and broader conflict resolution strategies in one of Asia’s most volatile borderlands.